Online Social Network Analysis using Machine Learning Techniques - Uttama Garg (International Journal of Advanced Science and Technology, 2020)
Now a days Social Media become the most powerful plateform to express your views and opinion. Orkut,Facebook, Twitter, Instagram are the mean of human life. Without social media or these social networking siteslife will be stopped, I think. Most of the working and non working people are registered in one of these sites allof the world. These social networking sites are the base of Sentiment Analysis and study of Opinion Mining. Thestudy of tehse opinions can lead to a decision or some marketing benefits. Because on can easily estimate thetheory of a human’s brain by studying his updates on these social networking sites. Now Machine LearningAlgorithm like Linear Regression, Logistic Regression, Support Vector Machine, Naïve Bayes[1] Algorithm canbe used to extract the conclusion of people’s opinion. To predict the most popular brand among Android andIOS smartphone, we are analyzing tweets in this paper.